2014
DOI: 10.7314/apjcp.2014.15.2.657
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between EGFR Mutation Status of Lung Cancer and Preoperative Factors - Are they Predictive?

Abstract: Background: The epidermal growth factor receptor (EGFR) mutation status of lung cancer is important because it means that EGFR-tyrosine kinase inhibitor treatment is indicated. The purpose of this prospective study is to determine whether EGFR mutation status could be identified with reference to preoperative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…Usuda et al reported that mutant EGFR is significantly associated with smaller tumor diameter in chest CT in addition to gender, pure or mixed GGO, adenocarcinoma, never-smoker (Usuda et al, 2014). Our results also showed that pStage and pT status were related to EGFR mutation in overall patients, but not men.…”
Section: Discussionsupporting
confidence: 73%
“…Usuda et al reported that mutant EGFR is significantly associated with smaller tumor diameter in chest CT in addition to gender, pure or mixed GGO, adenocarcinoma, never-smoker (Usuda et al, 2014). Our results also showed that pStage and pT status were related to EGFR mutation in overall patients, but not men.…”
Section: Discussionsupporting
confidence: 73%
“…In the study, the frequency of EGFR mutations was not associated with early stage disease (stage I to II) after adjusting for age, tumor differentiation, and histological subtype (OR, 1.46; 95% CI, 0.84–2.54; P = 0.18). Conflicting results were reported by Usuda et al [27] in a cohort of 148 Japanese patients with operable lung cancer. The clinical stage of EGFR mutant tumors was significantly earlier than that of wild-type tumors ( P = 0.016).…”
Section: Discussionmentioning
confidence: 85%
“…Most reports focused on the presence of any GGO or GGO proportion and some of the findings are conflicting. The definition of GGO proportion differs among studies and the following parameters have been used to calculate the GGO proportion: consolidation/tumor dimension ratio (33,34), GGO/tumor area ratio (35), area ratio of tumor on mediastinal windows to that on lung windows, GGO/tumor volume ratio (6,36,37), and the product of the dimension ratio of the tumor on mediastinal windows to that on lung windows to calculate the tumor shadow disappearance rate (TDR) (37-39).…”
Section: Molecular Pathology and Ct Featuresmentioning
confidence: 99%